INCIDENCE OF GRAIN MOLD ON SORGHUM IN MARATHWADA REGION - D. K. SHERKAR; A. M. CHAVAN (International Journal of Pharma and Bio Sciences, 2015)
Sorghum (Sorghum bicolar (L.) Moench) is one of cereal crop of the world. It is a good source of Carbohydrates. Sorghum is produced on a large scale in India and worldwide. This is an important cereal crop facing the problem of yield loss, because of biotic factors and abiotic factors. Grain mold disease is a serious biotic factor for yield loss in this crop. Due to grain mold disease maximum yield loss was occurring in sorghum. In India sorghum was cultivated in kharif and rabi season. In kharif season raining and humid condition fevers the development of this disease. In the present study infected sorghum panicles was collected from various regions of Marathwada in rainy season. Seed mycoflora were isolated by using blotter plate method and Agar plate method. 17 different fungus was isolated from infected sorghum, those are via Alternaria alternata, Alternaria sps, Aspergillus flavus, A. niger, A. paraciticus, A. terrus, Bipolaris sps, Cladosporium sps, Curvularia lunata, Fusarium maniliformae, Fusarium semitectum, penicillum sps, Phoma sorghina, Rhizopus stolonifer, Rhizopus sps, and trichothecium roseum . Disease incidence was calculated in both the methods of isolation.